Four persons envy-free division: a case study - Rahman, Farin; Mostafa, Mahjabeen; Rahman, M.M. Hafizur (2014)
In this paper we present an algorithm for 4 person envy free division. The theme of this division is that each and every person will not envious to other i.e. no one will receive larger piece. They will be satisfied with their own portion and will think that he or she received the largest piece. Here we present two possible procedures and we used as minimal cuts as possible.